Does long-term grazing cause cascading impacts on the soil microbiome in mountain birch forests? - Ahonen, Saija H. K. (Elsevier, 2025)
In subarctic mountain birch forests, reindeer grazing and moth outbreaks act as important biotic drivers of ecosystem functioning. We investigated how a long-term contrast in reindeer grazing regimes and short-term ungulate exclusion affected soil fungal and bacterial communities in mountain birch forests recovering from a recent moth outbreak. We separately described the impacts on microbial communities for organic and mineral soil layers. Differences in fungal communities were mainly explained by variations between grazing regimes, whereas the four-year exclusion of ungulates had little effect. Soil microbial communities showed a high level of specificity between organic and mineral layers. Our results suggest that long-term grazing may have cascading impacts, especially on ectomycorrhizal fungal communities. In contrast, ericoid mycorrhizal and saprotrophic fungal communities and soil bacterial communities were less affected by grazing and appeared to be more resilient to aboveground herbivory in mountain birch forests recovering from a moth outbreak.